2015
DOI: 10.1002/admi.201500505
|View full text |Cite
|
Sign up to set email alerts
|

Biohybrid Janus Motors Driven by Escherichia coli

Abstract: There has been a significant interest in the development of microswimmers for medical drug and cargo delivery, but the majority of current micromotors rely on toxic fuel sources and materials in their design making them irrelevant for biomedical applications. Bacteria represent an excellent motor alternative, as they are powered using their surrounding biological fluids. For a motile, biohybrid swimmer, Escherichia coli (E. coli) are integrated onto metal capped, polystyrene (PS) Janus particles. Fabrication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 51 publications
2
111
0
1
Order By: Relevance
“…As it has been previously demonstrated that bacteria display preferential adhesion to metals 47,48 and the negative charge of their cell wall favors their interactions with positive charged surfaces by van der Waals and electrostatic forces. 52,53 Thus, these interactions promote, in this particular case, the adhesion to the Au cap where the AgNPs are attached (Figure 4 As the microbots contain Fe as a sandwitched material (Au/Fe/Mg) on the particle, AgNPs coated Janus microbots are capable to remove the bacteria from contaminated solutions using their magnetic properties.…”
Section: Resultsmentioning
confidence: 95%
“…As it has been previously demonstrated that bacteria display preferential adhesion to metals 47,48 and the negative charge of their cell wall favors their interactions with positive charged surfaces by van der Waals and electrostatic forces. 52,53 Thus, these interactions promote, in this particular case, the adhesion to the Au cap where the AgNPs are attached (Figure 4 As the microbots contain Fe as a sandwitched material (Au/Fe/Mg) on the particle, AgNPs coated Janus microbots are capable to remove the bacteria from contaminated solutions using their magnetic properties.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, in comparison with previous reports of E. coli adhesion over metal-caped Janus particles or PLL mediated electrostatic adsorption, the specific bonding method reported in this paper is effective for longer duration biohybrid propulsion due to the increased bond stability. [11] The recipe designed in this study for biotin-streptavidin modification of Janus beads is superior in terms of irreversible, stable, and specific binding and the control over cell density of biohybrid microswimmers. [19] We also observed qualitatively that the cell orientation of biotin-streptavidin-modified Janus beads was more stable compared to the control surfaces.…”
Section: Doi: 101002/adhm201600155mentioning
confidence: 99%
“…Previous reports of E. coli adhesion to directly nanostructured metal cap of microbeads may have induced loss of bacterial flagellar motors which significantly reduce the propulsion speed compared to the one reported here in our study. [11] To validate that the Janus patterned and unpatterned bead propulsions were due to the attached bacteria motility, a control experiment was performed by coating 1, 3, and 10 μm microbeads with Pluronic F108. Pluronic F108 is a triblock copolymer surfactant that completely eliminates bacterial adhesion by creating cell repellent hydrophobic layer over microbeads.…”
Section: Communicationmentioning
confidence: 99%
“…77 For guided cell adhesion, directional swimming, and drug delivery, contained in a single biohybrid, a multifunctional biohybrid was developed. 78 Metal capped (Au, Pt, Fe, Ti) 2 μm and 600 nm polystyrene particles were coupled with Escherichia coli ( E. coli ) (Figure 7D,F). E. coli preferentially adhered only to the metal cap of the Janus particle without secondary surface modification 79 or antibodies 80 for simple and rapid biohybrid formation.…”
Section: Biohybrid Micromotorsmentioning
confidence: 99%